Pengabdian Masyarakat Melalui Sosialisasi Pengelolaan Limbah Plastik pada Destinasi Wisata Menggunakan Metode PAM - Purwo Subekti (JPMAT : Jurnal Pengabdian Kepada Masyarakat Aplikasi Teknologi, 2023)
Community service activities through socialization of the PAM method in managing plastic waste at tourist destinations in Rokan Hulu Regency, with in-depth material including the process of collecting plastic waste, transporting it to the final collection point at tourist locations and using plastic waste as raw material for products with economic value. Plastic waste management in tourist destination operational areas can partner with collectors to increase economic added value and as an effort to care for the environment. Apart from that, plastic waste is used as raw material to produce alternative energy.